(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2018)
In this article I investigate both what we can know about Dutch ways of dealing with the important ports in the western archipelago, a commercially rich and politically divided region, and what we think we know. I take a fresh look at the beginnings of their presence and at how relations were established and evolved. By employing a critical assessment of the documents produced during this period and comparing these with the scholarly findings in the historical literature, I aim to present an informed perspective of the nature of the different relationships. The documents have at least the merit of being contemporary and therefore reflect perceptions and conditions during this period. Closing alliances and treaties with the rulers of these ports was one way to break the Portuguese trade monopoly which ultimately led to rewriting the region’s narrative on the familiar lines of conquest.